The correlation of the intestinal with pharyngeal microbiota in early neonates - Wang, Xuejuan; Shao, Zhiying; Zhu, Minrong; Li, Bingjie; You, Mingyu; Chen, Xiaoqing (Frontiers in Microbiology, 2023)
The gut-lung axis has been well recognized as an important mechanism affecting intestinal and lung immunity, but few studies have been reported on the correlation of the intestinal with pharyngeal microbiota in early neonates, and the feeding patterns have been shown to be one of the main drivers of microbiota development. To explore the composition and function of intestinal and pharyngeal microbiota and to analyze the effect of limited formula feeding on the initial microbiota colonization in early full-term neonates, we characterized the stool and oropharyngeal microbiota of 20 healthy full-term newborns, sampled on day 0 and day 5-7 after birth, by 16S rRNA gene sequencing. Based on the sequencing results, a comparison was made of the compositions and functions of the intestinal and oropharyngeal microbiota for an analysis. At phylum level, Firmicutes, Actinobacteria, Proteobacteria and Bacteroidetes were the most abundant in both niches. At genus level, the species of pioneer bacteria in the intestine and oropharynx were rich, but low in abundance on day 0. On day 5-7, Bifidobacterium (25.40%) and Escherichia-Shigella (22.16%) were dominant in intestine; Streptococcus (38.40%) and Staphylococcus (23.13%), in the oropharynx. There were eight core bacteria genera in the intestine and oropharynx on day 5-7, which were Bifidobacterium, Escherichia-Shigella, Staphylococcus, Streptococcus, Bacteroides, Parabacteroides, Rothia, and Acinetobacter. As indicated by PICRUSt analysis, on day 5-7 the intestinal microbiota was more predictive than the oropharyngeal microbiota in transcription, metabolism, cell motility, cellular processes and signaling, and organismal system function in the KEGG pathway. When compared with exclusive breastfeeding, limited formula feeding (40-60%) had no significant effect on the composition of neonatal intestinal and oropharyngeal microbiota during the initial colonization period. Our results suggest that the initial colonization of microbiota is closely related to the ecological niche environment in the intestine and oropharynx, their core microbiota being closely correlated. Early limited formula feeding cannot have any significant effect on the initial colonization of microbiota in the intestine and oropharynx.